Developing research networks in schools: the role of network intentionality and research engagement - Cornelissen, Frank; McLellan, Ros; Daly, Alan (Frontiers in Education, 2024)
For many decades scholars argued that teachers needed to be research-informed and involved in educational research. This was seen as a new way to bridge the perceived gap between educational research and practice and as a promising avenue to improve teaching in schools.However, over the years it became evident that building such research engagement in schools is challenging (McIntyre, 2005; Farley-Ripple, May, Karpyn, Tilley & McDonough, 2018). The current call for teachers and schools to become more research-engaged is therefore by no means new, but is now resonating stronger than ever with efforts from school leaders to strengthen research impact and to improve education in schools (Author, 2014; Brown, 2015;